A papular eruption on the elbows in a patient with rheumatoid arthritis. (6th July 2021) - James, M.; Sioletic, S.; Creamer, D.
Abstract : Click https://wileyhealthlearning.com/#/online-courses/8063f3f8-b9a9-49f2-a3a7-0686d9d0a5dc for the corresponding questions to this CME article.